Historiografía y memoria colectiva tiempos y territorios - GODOY, Cristina comp. (NIÑO Y DAVILA, 2002)
Otros autores: DA SILVA CATELA, Ludmila; BRUERA, Matilde; FERNANDEZ ACEVEDO, Isabel; ANDRES, Beatriz; WANG, Diana; FEIERSTEIN, Daniel; MARTINEZ DE AGUIRRE, Elizabeth; PAMPINELLA, Silvia; MONTINI, Pablo; CONENNA, Claudio; SAITTAM, Sylvia; KAUFMANN, Carolina; AGUILA, Gabriela; VIANO, Cristina; FRANCESCUTTI, Pablo; MAURI NICASTRO, Roxana